The effect of research on life satisfaction in middle-aged and older adults: physical disability and physical activity as a parallel and serial mediation analysis - Pei-Shan Li; Chia-Jung Hsieh; Ya-Ling Shih; Ya-Ting Lin; Chieh-Yu Liu (BMC Geriatrics, 2023)
Abstract Background and objective Maintaining the life satisfaction of frail middle-aged and older adults when they experience physical disability, lower activity status, or complex conditions that are related to each other is now an urgent issue. Therefore, the purpose of this study was to provide evidence for the impact of frailty in middle-aged and older adults on life satisfaction under the simultaneous occurrence and correlation of physical disability and physical activity status. Methods Data from the 2015 Taiwan Longitudinal Study in Ageing (TLSA) were analyzed by PROCESS in SPSS to explore three different mediation models (N = 4,421). The first was a parallel mediation model for exploring life satisfaction in middle-aged and older adults with frailty through physical disability or physical activity. The second was a serial mediation model for examining physical disability and physical activity in causal chains linked with a specific direction of flow and to test all combinations. The third was a moderated mediation model for testing whether the indirect effect of frailty status on life satisfaction through physical disability or physical activity was moderated by age stratification. Results Physical disability and physical activity partially mediated the relationship between frailty status and life satisfaction (IEOVERALL = -0.196, 95% CI: -0.255 to -0.139). The causal path with the highest indirect effect was found to be that between frailty and physical disability; increased frailty led to higher physical disability, which in turn affected physical activity, leading to lower life satisfaction (IE = 0.013, 95% CI: 0.008 to 0.019). The different stratifications by age significantly increased the mediating effect of physical activity (Index of Moderated Mediation = -0.107, SE = 0.052, 95% CI: -0.208 to -0.005) but did not reduce the mediating effect of physical disability. Conclusion This study provides evidence that physical activity and physical disability influence the development of frailty. It also has a significant impact on the life satisfaction of middle-aged and older adults.